Review of Mutual Funds Investment in India - et. al., Govindappa Mani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Indian mutual fund's industry, which started its excursion with the foundation of the Unit Trust of India in 1964, has seen unobtrusive development lately. There has been developing both regarding AUM just as the assortment of items advertised. As on December 2015, the investors in India have a choice to look over in excess of 1,000 of mutual funds plans spread across 44 fund houses with a complete AUM estimation of '13.46 lakh crores. The passage of unfamiliar players has prompted the presentation of an assortment of inventive items to suit the developing necessities of Indian investors. The Indian mutual fund's industry was discovered to be overwhelmed by institutional investors.